The Dynamics of Selenium Uptake by Maize (Zea mays L.) - Aldona Płaczek; Barbara Patorczyk-Pytlik (Agronomy, 2021)
The dynamics of selenium (Se) uptake by two maize varieties (Zea mays L.) were assessed under two selenium doses (0.1 and 0.2 mg kg−1 of soil) applied to the soil. The addition of Se increased the biomass yield of the Se-susceptible variety (Bielik), while significantly decreasing the yield of the Se-resistant variety (Lober), and this suppression was stronger at the higher Se dose. The content and uptake of selenium by maize also increased with the Se dose, and the Bielik variety proved to be more effective. In terms of crop quality for animal nutrition, the optimal Se content (330–365 µg kg−1) was reached after 81 days of vegetation under the lower Se dose only, while the higher treatment led to excessive Se accumulation in maize biomass.